Microfibers Pollution Associated with Disposable PPE Products Driven by the COVID-19 Pandemic and Its Environmental Repercussions (Chapter 7) - Forero Lopez, A. D.; De la Torre, Gabriel Enrique; Fernandez Severini, Melisa Daiana; Rimondino, Guido; Spetter, Carla (CRC Press, Taylor & Francis Group, 2024)
Este libro se encuentra embargado, puede comunicarse con el autor Guido Rimondino: grimondino@unc.edu.ar